Geopolymer Concrete: Sustainable Cementless Concrete - Lloyd, Natalie; Rangan, Vijaya (Laser Park Publishing House, 2010)
Geopolymer results from the reaction of a source material that is rich in silica and alumina with alkaline liquid. It is essentially cement free concrete. This material is being studied extensively and shows promise as a greener alternative to ordinary Portland cement concrete. Research is shifting from the chemistry domain to engineering applications and commercial production of geopolymer concrete. It has been found that geopolymer concrete has good engineering properties with a reduced carbon footprint resulting from the total replacement of ordinary Portland cement. The research undertaken at Curtin University of Technology has included studies on geopolymer concrete mix design, structural behavior and durability. This paper presents the results from recent studies which focused on mix design development to enhance workability and strength of geopolymer concrete. The research was conducted with the view to using geopolymer concrete for pre-cast structural applications. The influence of factors such as, curing temperature and regime, aggregate shape, strengths, moisture content, preparation and grading, and the addition of super-plasticizers, on workability and strength are presented. The paper also includes brief details of some recent applications of geopolymer concrete.